SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN PENDIDIKAN MENGGUNAKAN METODE ELECTRE DI SMP NEGERI 2 RENGAT BARAT - Anita Febriani; Rika Melyanti; Gunawan (Jurnal Ilmu Komputer, 2022)
At SMP Negeri 2 Rengat Barat every year there is educational assistance from BAZNAS, Indragiri Hulu Regency, several years ago in determining decision making based on a proposal from the homeroom teacher by proposing a certain number of students with modest criteria so that it was difficult to determine who received educational assistance. By using the Elimination Et Choix la Realite (ELECTRE) method to facilitate the process and to be transparent and objective in making decisions on the recipients of educational assistance, criteria are made, including: Student attendance, attitude at school, GPA or report cards and Income Certificate issued by the Village or lurah and each criterion is given a score or value from 1 to 5. The researcher uses the Elimination Et Choix la Realite (ELECTRE) method using the Laravel application, the admin will be easy to input data and process and the results are quickly visible. The results of calculations through the system, the admin provides information to the principal to see data that are eligible to receive educational assistance. The results of the calculations to assist the principal's decision, after approval, a printing process will be carried out, then the recipients of educational assistance will be informed through the bulletin board, homeroom teacher, or class group. With the application created and practiced by the Admin, the results obtained are very helpful for all schools to determine the recipients of educational assistance because this system shows transparent and objective results. With this electre application, the school accepts it to be used this year as well as for the coming year, because the school realizes the importance of this application which can assist in objective decisions in determining recipients of educational assistance..